Arab Republic of Egypt : Selected Issues. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper examines whether Egypt's current account and exchange rate are in broad equilibrium. The paper analyzes areas of fiscal spending that have the biggest saving potential in a cross-country perspective. An assessment of Egypt's real exchange rate is presented. The paper uses data envelopment analysis to analyze the efficiency in public spending on health, education, and social protection relative to comparable countries. The results suggest significant scope to improve efficiency in all three social areas, and that room for fiscal savings is particularly apparent in social protection and education.